2002
DOI: 10.1124/mol.62.2.297
|View full text |Cite
|
Sign up to set email alerts
|

trans-Activation and Repression Properties of the Novel Nonsteroid Glucocorticoid Receptor Ligand 2,5-Dihydro-9-hydroxy-10-methoxy-2,2,4-trimethyl-5-(1-methylcyclohexen-3-y1)-1H-[1]benzopyrano[3,4-f]quinoline (A276575) and Its Four Stereoisomers

Abstract: Glucocorticoids are potent anti-inflammatory and immunosuppressant agents. However, they also produce serious side effects that limit their usage. It has been proposed that antiinflammatory properties of glucocorticoids are caused mostly by repression of activator protein 1-and nuclear factor ␤-stimulated synthesis of inflammatory mediators, whereas most of their adverse effects are associated with trans-activation of genes involved with metabolic processes. Our laboratories have sought to discover novel gluco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 23 publications
0
22
0
Order By: Relevance
“…The development of selective GR agonists (28) that target the transrepressive effects of GCs over the tranasctivating actions looks promising (29,30) but a clinical drug has not yet been delivered. Numerous selective 11β-HSD1 inhibitors have been developed and many tested in phase II studies (12,13); their evaluation in patients with Cushing syndrome will be of great interest.…”
Section: Discussionmentioning
confidence: 99%
“…The development of selective GR agonists (28) that target the transrepressive effects of GCs over the tranasctivating actions looks promising (29,30) but a clinical drug has not yet been delivered. Numerous selective 11β-HSD1 inhibitors have been developed and many tested in phase II studies (12,13); their evaluation in patients with Cushing syndrome will be of great interest.…”
Section: Discussionmentioning
confidence: 99%
“…"transactivation", which is thought to be responsible for most of the adverse reactions [3], and "transrepression", which is considered to mediate numerous desirable anti-inflammatory and immunomodulating effects [45]. Hence, "dissociating glucocorticoids" or so called "selective glucocorticoid receptor agonists (SEGRA's)" are in the development pipeline.…”
Section: Selective Glucocorticoid Receptor Agonists (Segra's)mentioning
confidence: 99%
“…However, in the last years an increasing number of SEGRA's has been described. A very interesting substance is for example A276575 and its four enantiomeres [45], all ligands that bind with the same affinity to the cGCR as dexamethasone does. These novel GCR ligands repress IL-1α-induced IL-6 production.…”
Section: Selective Glucocorticoid Receptor Agonists (Segra's)mentioning
confidence: 99%
“…Despite showing initial promise in dissociation of GC mediated gene activation and repression, the in-vivo effects were more disappointing and the drug did not make it into clinical trials (Belvisi et al, 2001). Other drugs such as A276575 have again shown promise but fared little better (Lin et al, 2002). The only SEGRA in clinical trials at the moment is ZK 245186 which is in Phase III trials for topical use post cateract surgery after initial results from animal models showed promise (Proksch et al, 2011).…”
Section: Segrasmentioning
confidence: 99%